Internet, humor, and nation in Latin America - Fernández L'Hoeste, Héctor D. 1962-; Poblete, Juan 1962- (University of Florida Press, 2024)
"This volume provides a comprehensive Latin American perspective on the role of humor in the Spanish- and Portuguese-language internet, highlighting how online humor influences politics and culture in Latin America"--
Keywords: Humor; Demokratie; Internet; Alltag; Lateinamerika; Politics and culture / Latin America / Humor; Social media / Latin America / Politics and government / Humor; Political science / Latin America / Humor; Politics, Practical / Latin America / Humor; Spanish wit and humor / Political aspects / History and criticism; Portuguese wit and humor / Political aspects / History and criticism; Latin America / Politics and government / Humor; Politique et culture / Amérique latine / Humour; Humour espagnol / Aspect politique / Histoire et critique; Amérique latine / Politique et gouvernement / Humour; POLITICAL SCIENCE / Political Process / Media & Internet; SOCIAL SCIENCE / Media Studies; Political science / Humor; Politics and government / Humor; Latin America; Criticism, interpretation, etc; Aufsatzsammlung